Methods of Standard Rates of Financial Expenses Calculation on Landscaped Areas Maintenance (on the example of St. Petersburg, Russia) - Skachkova, Maria Evgenievna; Lepikhina, Olga Jurjevna (International Journal of Economics and Financial Issues, 2016)
Relevance of research is caused by need of optimization of the expenditure of budgetary funds of St. Petersburg in the field of gardening. The article is devoted to development of system of indicators for identification of volumes of works per unit of measurement, necessary to form costs for works on maintenance of objects and the territories of green plantings of St. Petersburg. Main methods to research of the matter were natural and analytical methods which have allowed revealing the main problems of management of the territories and objects of green plantings of the megalopolis. Also the method of the statistical analysis was applied to sample some 123 objects of green plantings of St. Petersburg. The system of indicators to calculate objectively and reasonably standard rates of finance costs on maintenance of objects and the territories of green plantings of St. Petersburg has been identified. To control results the method of the comparative analysis was used. Problems of management of the territories and objects of green plantings of megalopolises are revealed; the unique system of indicators for the purposes of forming of standard rates of finance costs for works on maintenance of objects and the territories of green plantings of megalopolises is provided; recommendations about enhancement of system of certification of green plantings are proved. The developed system of indicators has been used by Committee for economic policy and strategic planning of St. Petersburg. Keywords: green plantings, maintenance, finance costs, accounting, certification JEL Classifications: M41, Q10